Improper co-authorship in common crimes - Sánchez Pérez, Claudia Patricia (DIXI, 2019)
Purpose: This reflection article focuses on the involvement of persons in the commission of the punishable conduct. It is said that when several persons carry out the criminal act, it is essential to identify the degree of criminal responsibility that corresponds to each one, according to their contribution. The figure of the improper co-operator in common crimes will be analyzed specifically. Description: The causes, consequences and legal remedies for those involved in the commission of the punishable conduct are described according to their degree of responsibility, avoiding the use by the Prosecutor’s Office of charges with exacerbated penalties. Point of view: There are valid legal, doctrinal and jurisprudential elements to make the right distinctions on the degree of responsibility for the intervention in the commission of punishable conduct. Nevertheless, these elements are not enforced by the prosecution agency or by the lawyer in his role as defender, accepting the formulation of charges without the verification of each of the elements that structure the improper co-authorship. Conclusions: Keep in mind the structural elements of improper co-authorship and the interpretation of its contents according to the law, the doctrine and the jurisprudence on the functional domain of the act and the restrictive concept of author. Based on this, it follows that taking into account the parameters already established, when differentiating improper co-authorship from other forms of participation especially that of the accomplice, leads to the formulation of charges and the merit of penalties proportional to the actual participation of a person in the commission of the punishable conduct.